2006
DOI: 10.1002/jbt.20118
|View full text |Cite
|
Sign up to set email alerts
|

Temporal kinetics and concentration–response relationships for induction of CYP1A, CYP2B, and CYP3A in primary cultures of beagle dog hepatocytes

Abstract: Compared to other species, little information is available on the xenobiotic-induced regulation of cytochrome P450 enzymes in the beagle dog. Dogs are widely used in the pharmaceutical industry for many study types, including those that will impact decisions on compound progression. The purpose of this study was (1) to determine the temporal kinetics of drug-induced changes in canine CYP1A, CYP2B, and CYP3A mRNA and enzymatic activity, and (2) to characterize concentration-response relationships for CYP1A2, CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…strate and inducer specificities between CYP3A4 and 3A5, PB induces CYP3A4 but not CYP3A5 gene expression (Matsunaga et al, 2004;Busi and Cresteil, 2005;Pelkonen et al, 2008;Ince et al, 2013). In the present study, all cattle CYP3A isoforms were induced by PB, similar to its effect in the domestic dog, in which PB increased CYP3A12 and 3A26 mRNA levels (Graham et al, 2006). In cattle, the order of magnitude of PB induction was two-to four-times the control value and comparable to the more general CYP3A pattern of up-regulation (Zancanella et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…strate and inducer specificities between CYP3A4 and 3A5, PB induces CYP3A4 but not CYP3A5 gene expression (Matsunaga et al, 2004;Busi and Cresteil, 2005;Pelkonen et al, 2008;Ince et al, 2013). In the present study, all cattle CYP3A isoforms were induced by PB, similar to its effect in the domestic dog, in which PB increased CYP3A12 and 3A26 mRNA levels (Graham et al, 2006). In cattle, the order of magnitude of PB induction was two-to four-times the control value and comparable to the more general CYP3A pattern of up-regulation (Zancanella et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…Among xenobiotics, the non-specific and pleiotropic CYP inducer phenobarbital (PB) has been shown to increase hepatic CYP3A mRNA levels and apoprotein amounts in cattle (Zancanella et al, 2012), and similarly in humans, rodent model species, dogs and pigs (Madan et al, 2003;Anakk et al, 2004;Graham et al, 2006;Magnusson et al, 2006;Puccinelli et al, 2010). In contrast, unexpected results have been observed following the exposure to a known human CYP3A inducer like dexamethasone (Greger and Blum, 2007;Cantiello et al, 2009).…”
Section: Introductionmentioning
confidence: 84%
“…The in vitro EC 50 values for BNF induction of CYP1A activity obtained in hepatocytes of dog (Graham et al, 2006), rat (Madan et al, 1999), and human (unpublished data cited in Graham et al, 2006) were 7.8, 1.5, and 4.2 M, respectively. BNF plasma protein binding in the rat is 96% (Adedoyin et al, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, DDIs caused by CYP induction may be best assessed with both rhesus monkeys (Macaca mulatta) and cynomolgus monkeys in light of the recent extensive studies of DDIs in these species after treatment with standard CYP3A inducers (55,56) and increased mechanistic understanding from those endeavors. Likewise, beagle dogs may have similar potential to estimate CYP induction based on the information collected from a number of studies (57)(58)(59). It has been reported that the induction of dog CYP1A, CYP2B, and CYP3A exhibits characteristics that are intermediate to those of rodent and human (59).…”
Section: Metabolism Modelsmentioning
confidence: 98%
“…Likewise, beagle dogs may have similar potential to estimate CYP induction based on the information collected from a number of studies (57)(58)(59). It has been reported that the induction of dog CYP1A, CYP2B, and CYP3A exhibits characteristics that are intermediate to those of rodent and human (59). Kyokawa et al (60) also reported the induction of beagle dog intestinal CYP3A12 by rifampin at a dose (10 mg/kg/day) comparable to the clinical dose for humans (600 mg/man/day).…”
Section: Metabolism Modelsmentioning
confidence: 99%